The Sicilian Wolf: Genetic Identity of a Recently Extinct Insular Population - Francesco M. Angelici; Marta M. Ciucani; Sabrina Angelini; Flavia Annesi; Romolo Caniglia; Riccardo Castiglia; Elena Fabbri; Marco Galaverni; Davide Palumbo; Gloria Ravegnini; Lorenzo Rossi; Agatino M. Siracusa; et al. (2019)
Historically, many local grey wolf (Canis lupus) populations have undergone substantial reductions in size or become extinct. Among these, the wolf population once living in Sicily, the largest island in the Mediterranean Sea, was completely eradicated by human activity in the early decades of the 20th century. To gain a better understanding of the genetic identity of the Sicilian wolf, we used techniques for the study of ancient DNA to analyze the mitochondrial DNA of six specimens stored in Italian museums. We were able to amplify a diagnostic mtDNA fragment of the control region (CR) in four of the samples. Two of the samples shared the same haplotype, differing by two substitutions from the currently most diffused Italian wolf haplotype (W14) and one substitution from the only other Italian haplotype (W16). The third sample showed a previously unreported wolf-like haplotype, and the fourth a haplotype commonly found in dogs. All of the wolf haplotypes analyzed in this study belonged to the mitochondrial haplogroup that includes haplotypes detected in all the known European Pleistocene wolves and in several modern southern European populations. Unfortunately, this endemic island population, which exhibited unique mtDNA variability, was definitively lost before it was possible to understand its taxonomic uniqueness and conservational value.